The effect of food additive on physicochemical characteristics of seaweed stick snack and consumer acceptance - Sumartini; Sellen Gurusmatika; Wan Amira (jurnal1, 2021)
Seaweed is considered high class marine and fisheries sector in international demand for its derivative products. One of traditional use of seaweed as food is stick snack which is widely consumed due to its crunchiness and deliciousness. The objective of this study was to characterize the proximate analysis, hardness, and sensory perception of stick snack derived from seaweed. Seaweed stick were prepared with varying food additives such as sodium acid phyorposphate (SAPP), steaoryl lactylate (SSL), sodium bicarbonate (NaHCO3), and control (without addition of food additives). The results confirmed that the use of food additives induce change in proximate, hardness, and sensory perception. Seaweed stick with addition NaHCO3 has the highest fat content while seaweed stick with addition of SAPP has the highest crispness. In addition, sensory test showed that seaweed stick with addition with NaHCO3 provide the highest acceptance in texture and flavour.